2008
DOI: 10.1007/s10764-007-9138-4
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Utilization of Three Sympatric Cheirogaleid Lemur Species in a Littoral Rain Forest of Southeastern Madagascar

Abstract: I compared the habitat utilization in 3 sympatric species of Cheirogaleidae (Microcebus murinus [81 g], Cheirogaleus medius [183 g] and Cheirogaleus major [362 g]) in a littoral rain forest in southeastern Madagascar during 3 rainy seasons.Females of promiscuous Microcebus murinus had small home ranges and the males had large overlapping home ranges. Home ranges of family groups of monogamous Cheirogaleus medius and C. major overlapped extensively. Home ranges of all 3 species overlapped completely in the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 50 publications
4
50
0
Order By: Relevance
“…Seasonal variation in usage patterns of sleeping sites has been reported for bats as well as marsupials (e.g. Cockburn & Lazenby-Cohen 1992;Kerth et al 2001) but not for lemurs, probably a result of the short-term studies that have previously been conducted in this group (Radespiel et al 1998Lahann 2008). The shift in preferences observed in our study mirrors the change in temperature fluctuations between the two seasons and the range of temperatures experienced was significantly smaller during the rainy than the dry season at our study site.…”
Section: Thermoregulatory Demands and Sleeping Sitessupporting
confidence: 71%
See 1 more Smart Citation
“…Seasonal variation in usage patterns of sleeping sites has been reported for bats as well as marsupials (e.g. Cockburn & Lazenby-Cohen 1992;Kerth et al 2001) but not for lemurs, probably a result of the short-term studies that have previously been conducted in this group (Radespiel et al 1998Lahann 2008). The shift in preferences observed in our study mirrors the change in temperature fluctuations between the two seasons and the range of temperatures experienced was significantly smaller during the rainy than the dry season at our study site.…”
Section: Thermoregulatory Demands and Sleeping Sitessupporting
confidence: 71%
“…However, if sleeping sites are a limiting resource for females with dependent offspring this may also explain the sex-specific differences in sleeping site usage patterns found in grey mouse lemurs. Previous studies have shown that males tend to use less protected sleeping sites, often resting in open vegetation, and changing their sleeping sites more frequently than females in this species (Radespiel et al 1998;Lahann 2008). As such sites are unsuitable for raising offspring, females may be forced to form groups to monopolize suitable sleeping sites.…”
mentioning
confidence: 96%
“…Energy saving might also explain the relatively small home ranges of sportive lemurs-about 1 ha for L. edwardsi (see Albignac 1981;Warren and Crompton 1997) and L. ruficaudatus (Zinner et al 2003), and 0.18 ha for female and 0.33 ha for male L. leucopus (see Dröscher and Kappeler 2013). The much smaller grey mouse lemur (Microcebus murinus), with its broad diet, has similar home ranges of 0.7-1.6 ha for females and 2.8-4.8 ha for males in dry deciduous forest (Eberle and Kappeler 2004;Lahann 2008;Radespiel 2000). With a median size of 0.38 ha, the home ranges of the Sahamalaza sportive lemurs we observed were similar in size to those found for the white-footed sportive lemur (Dröscher and Kappeler 2013).…”
Section: Observation Time (H)mentioning
confidence: 99%
“…The Sahamalaza sportive lemur is Critically Endangered (Davies and Schwitzer 2013;IUCN 2014), and was included on the list of the World's Top 25 Most Endangered Primates 2006-2008(Olivieri et al 2007a. The Sahafary sportive lemur, L. septentrionalis, occurring in far northern Madagascar, has been on the list of the World's 25 Most Endangered Primates since 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Four species use leaf nests exclusively (Microcebus griseorufus , Microcebus myoxinus , Mirza coquereli and Mirza zaza) [Kappeler, 1998;Kappeler et al, 2005;Génin, 2008]. Tree holes are used exclusively or in combination with leaf nests by the majority of species (Cheirogaleus major , Cheirogaleus medius , Microcebus berthae , Microcebus murinus , Microcebus ravelobensis , Microcebus rufus and Phaner pallescens) [Martin, 1973;Wright and Martin, 1995;Radespiel, 1998;Schmid, 1998;Müller, 1999a;Schmelting, 2000;Schwab, 2000;Fietz and Dausmann, 2003;Radespiel et al, 2003;Schülke and Kappeler, 2003;Dammhahn and Kappeler, 2005;Dausmann et al, 2005;Rasoazanabary, 2006;Lahann, 2007Lahann, , 2008; Deppe et al, 2008]. Although the hairy-eared dwarf lemur (Allocebus trichotis) has previously been observed to use tree holes and the characteristics of a few of these cavities have been reported, it is important for the survival of this enigmatic species to gather additional information on this aspect of its habitat needs [Meier and Albignac, 1991;Rakotoarison et al, 1997;Goodman and Raselimanana, 2002].…”
Section: Foliamentioning
confidence: 99%